Successful treatment with matched unrelated donor peripheral blood stem cell transplantation for very severe aplastic anemia in presence of active infections: A case report. Issue 14 (April 2020) - Huang, Yu-Rong; Xie, Cai-Qin; Tong, Jie-Feng; Zhang, Xiao-Hong; Xu, Yang; Yuan, Xiang-Gui
Abstract: Rationale: Very severe aplastic anemia (vSAA) with active infections is always fatal. Adequate infection control before hematopoietic stem cell transplantation is recommended. Patient concerns: A 38-year-old woman with vSAA suffered from acute perforated appendicitis and invasive pulmonary fungal infection, and she failed to respond to intense antimicrobial therapies. Diagnosis: She was diagnosed with refractory vSAA with stubborn acute perforated appendicitis and invasive pulmonary fungal infection. Interventions: We successfully completed an emergent reduced intensity conditioning-matched unrelated donor (MUD)-peripheral blood stem cell transplantation (PBSCT) as a salvage therapy in the presence of active infections. The conditioning regimens consisted of reduced cyclophosphamide 30 mg/kg/day from day-5 to day-3, fludarabine 30 mg/m 2 /day from day-5 to day-3 and porcine-antilymphocyte immunoglobulin 15 mg/kg/day from day-4 to day-2 without total body irradiation. Cyclosporin A, mycophenolate mofetil and short-term methotrexate were administered as graft-versus-host disease (GVHD) prophylaxis. Neutrophils and platelets were engrafted on day+15 and day+21. Appendiceal abscess and severe pneumonia developed after neutrophil engraftment, which were successfully managed with intense antimicrobial therapy and surgical intervention. Outcomes: Only limited cutaneous chronic GVHD was observed 5 months after transplantation. The patient still lives in a good quality of life 2 years after transplantation. Lessons: Active infections may be no longer a contraindication to hematopoietic stem cell transplantation for some patients with vSAA.